(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Rheumatoid Arthritis (RA) is an autoimmune rheumatic disease characterized by chronic erosive arthritis and systemic inflammatory changes in internal organs, leading to early disability and a reduced quality of life for patients. Modern imaging techniques have marked a new milestone not only in the diagnosis of diseases but also in the evaluation of their progression and outcome prediction. Joint ultrasound examination in RA is currently regarded as one of the most accessible and widely used instrumental diagnostic methods. This review of international literature provides a detailed analysis of publications dedicated to ultrasound examination of joints in RA. The findings are contradictory and often question the informativeness of this method. The abundance of original publications reflects the significant interest of rheumatologists in this technique. The current perspectives on the pathogenetic rationale, diagnostic value, and prognostic potential of ultrasound use in RA patients are presented. Issues of diagnostic procedure methodology, the necessity of using power Doppler imaging, and modern semi-quantitative scales for assessing the severity of inflammation are discussed. Existing international guidelines for the use of ultrasound in RA are outlined, emphasizing the importance of this imaging modality.